2008
DOI: 10.1111/j.1751-3928.2008.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Element Enrichment in Late Archean Manganese Deposits from the Iron Ore Group, East India

Abstract: The major, trace and rare earth element (REE) composition of Late Archean manganese, ferromanganese and iron ores from the Iron Ore Group (IOG) in Orissa, east India, was examined. Manganese deposits, occurring above the iron formations of the IOG, display massive, rhythmically laminated or botryoidal textures. The ores are composed primarily of iron and manganese, and are low in other major and trace elements such as SiO 2 , Al 2 O 3 , P 2 O 5 and Zr. The total REE concentration is as high as 975 ppm in manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…It is noteworthy that, the ΣREE contents of these manganese deposits are significantly high, such as Zunyi (ΣREE=509.54 ppm, tuffaceous clay rock=1394 ppm), Shuicheng (ΣREE=712 ppm), Qianxi (ΣREE=1175.11 ppm) and Xuanwei (ΣREE=493 ppm) (Table 4; Liu et al, 2008;Yang et al, 2009;Xu et al, 2018). This is similar to the hydrothermal manganese deposits in Sardinia, Western Italy (REE= 3309.15 ppm) (Mongelli et al, 2013), the Neptuno manganese deposits in the Santa Rosalía basin and adjacent areas in Baja California Sur, México (REE=563.10 ppm) (Del RioSalas et al, 2008), and the late Archean hydrothermal HREE-rich manganese deposit in eastern India (REE highest=563.10 ppm) (Mohapatra et al, 2006;Mishra et al, 2006;Moriyama et al, 2008). Hence, these obvious geological and geochemically characteristics indicate that manganese mineralization and REEs enrichment have been related to hydrothermal activity in Zunyi and its adjacent areas during the middle to late Permian.…”
Section: Sources Of the Rare Earth Elements (Rees)supporting
confidence: 71%
“…It is noteworthy that, the ΣREE contents of these manganese deposits are significantly high, such as Zunyi (ΣREE=509.54 ppm, tuffaceous clay rock=1394 ppm), Shuicheng (ΣREE=712 ppm), Qianxi (ΣREE=1175.11 ppm) and Xuanwei (ΣREE=493 ppm) (Table 4; Liu et al, 2008;Yang et al, 2009;Xu et al, 2018). This is similar to the hydrothermal manganese deposits in Sardinia, Western Italy (REE= 3309.15 ppm) (Mongelli et al, 2013), the Neptuno manganese deposits in the Santa Rosalía basin and adjacent areas in Baja California Sur, México (REE=563.10 ppm) (Del RioSalas et al, 2008), and the late Archean hydrothermal HREE-rich manganese deposit in eastern India (REE highest=563.10 ppm) (Mohapatra et al, 2006;Mishra et al, 2006;Moriyama et al, 2008). Hence, these obvious geological and geochemically characteristics indicate that manganese mineralization and REEs enrichment have been related to hydrothermal activity in Zunyi and its adjacent areas during the middle to late Permian.…”
Section: Sources Of the Rare Earth Elements (Rees)supporting
confidence: 71%
“…Indeed, rhodochrosite is a major manganese mineral in hydrothermal manganese deposits (e.g., ref. 47), and Archean manganese-rich rocks show a strong signal of hydrothermal input (48,49). It is worth mentioning that Archean sedimentary rocks have experienced at least low-grade metamorphism which may undermine the preservation of rhodochrosite via decarbonation to form MnO or Mn-silicate, which often cooccurs with rhodochrosite in metamorphosed sediments (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Grant et al [37],Avasthy [38],Sarkar [39] and Raha and Moitra [40] reported algal stromatolites and spheroidal & filamentous microfossils in the BIF and manganese ore horizon of the Noamundi basin. Beukes et al [25] studied the Fe-ores of the Noamundi basin and concluded that the original magnetite rich Fe-ore protolith evolved to high grade hematite ore in three stages i.e.…”
Section: Discussionmentioning
confidence: 99%